2014
DOI: 10.1002/2013jd021079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sources and meteorology on particulate matter in the Western Mediterranean Basin: An overview of the DAURE campaign

Abstract: DAURE (Determination of the Sources of Atmospheric Aerosols in Urban and Rural Environments in the Western Mediterranean) was a multidisciplinary international field campaign aimed at investigating the sources and meteorological controls of particulate matter in the Western Mediterranean Basin (WMB). Measurements were simultaneously performed at an urban-coastal (Barcelona, BCN) and a rural-elevated (Montseny, MSY) site pair in NE Spain during winter and summer. State-of-the-art methods such as 14 C analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 113 publications
(166 reference statements)
4
72
0
Order By: Relevance
“…Such scenarios are characterized by anticyclonic conditions which favour the accumulation of pollutants close to the emission sources, and the subsequent transport of pollutants towards the station with the daily increase in the PBL. Pandolfi et al (2014b) and Pey et al (2010) reported high nitrate concentrations during these atmospheric conditions at MSY, in agreement with the increased contributions of secondary nitrate shown in Fig. 3b during this time of the year.…”
Section: Seasonal Variation Of Source Contributions To Pm 10supporting
confidence: 86%
See 1 more Smart Citation
“…Such scenarios are characterized by anticyclonic conditions which favour the accumulation of pollutants close to the emission sources, and the subsequent transport of pollutants towards the station with the daily increase in the PBL. Pandolfi et al (2014b) and Pey et al (2010) reported high nitrate concentrations during these atmospheric conditions at MSY, in agreement with the increased contributions of secondary nitrate shown in Fig. 3b during this time of the year.…”
Section: Seasonal Variation Of Source Contributions To Pm 10supporting
confidence: 86%
“…Moreover, the reduced contribution from the PBL in winter due to frequent thermal inversions also contributed to the relatively low PM 10 mass concentration observed at MSY, and especially at MSA (Pandolfi et al, 2014a). The PM 10 concentration peak observed in February and March at MSY is remarkable and might be attributed to the winter regional pollution episodes typical of the WMB (Pandolfi et al, 2014b). Such scenarios are characterized by anticyclonic conditions which favour the accumulation of pollutants close to the emission sources, and the subsequent transport of pollutants towards the station with the daily increase in the PBL.…”
Section: Seasonal Variation Of Source Contributions To Pm 10mentioning
confidence: 96%
“…Under these conditions the PBL height mostly determines the dilution of pollutants around the emission sources and the degree of pollution at more elevated/regional areas in the WMB (e.g. Jorba et al, 2013;Pandolfi et al, 2014). In summer, due to the intense and rapid solar heating of the lower atmospheric layers, convergence of surface winds from the coast to the central IP plateau injects polluted air into the middle troposphere up to 3.5-5 km (Millán et al, 1997;Pérez et al, 2004).…”
Section: Main Meteorological Patternsmentioning
confidence: 99%
“…Over this region, arrival of natural and anthropogenic aerosols as a result of long-range transport from Africa and Europe is frequent (e.g., Pey et al, 2013;Querol et al, 2009;Ripoll et al, 2014;Rodríguez et al, 2001) and accumulation and recirculation processes are frequently observed (Rodriguez et al, 2002). The sources and meteorological controls of PM in the regional background of the WMB have been recently investigated during the DAURE (Determination of the sources of atmospheric Aerosols in Urban and Rural Environments in the western Mediterranean) study (Pandolfi et al, 2014a) using an AMS and 14 C analyses (Crippa et al, 2014;. Furthermore, Ripoll et al (2015) studied the PM 1 and PM 10 chemical composition with daily time resolution in the continental and regional background environments in the WMB.…”
Section: Introductionmentioning
confidence: 99%